Role of systemic immune-inflammation index in patients treated with salvage radical prostatectomy - Rajwa, Pawel; Schuettfort, Victor M; Quhal, Fahad; Mori, Keiichiro; Katayama, Satoshi; Laukhtina, Ekaterina; Pradere, Benjamin; Motlagh, Reza Sari; Mostafaei, Hadi; Grossmann, Nico C; Aulitzky, Andreas; Paradysz, Andrzej; et al. (World journal of urology, 2021)
PURPOSE: To examine the predictive and prognostic value of preoperative Systemic Immune-inflammation Index (SII) in patients with radio-recurrent prostate cancer (PCa) treated with salvage radical prostatectomy (SRP). MATERIALS AND METHODS: This multicenter retrospective study included 214 patients with radio-recurrent PCa, treated with SRP between 2007 and 2015. SII was measured preoperatively (neutrophils × platelets/lymphocytes) and the cohort was stratified using optimal cut-off. Uni- and multivariable logistic and Cox regression analyses were performed to evaluate the predictive and prognostic value of SII as a preoperative biomarker. RESULTS: A total of 81 patients had high preoperative SII (≥ 730). On multivariable logistic regression modeling, high SII was predictive for lymph node metastases (OR 3.32, 95% CI 1.45-7.90, p = 0.005), and non-organ confined disease (OR 2.55, 95% CI 1.33-4.97, p = 0.005). In preoperative regression analysis, high preoperative SII was an independent prognostic factor for cancer-specific survival (CSS; HR 10.7, 95% CI 1.12-103, p = 0.039) and overall survival (OS; HR 8.57, 95% CI 2.70-27.2, p < 0.001). Similarly, in postoperative multivariable models, SII was associated with worse CSS (HR 22.11, 95% CI 1.23-398.12, p = 0.036) and OS (HR 5.98, 95% CI 1.67-21.44, p = 0.006). Notably, the addition of SII to preoperative reference models improved the C-index for the prognosis of CSS (89.5 vs. 80.5) and OS (85.1 vs 77.1). CONCLUSIONS: In radio-recurrent PCa patients, high SII was associated with adverse pathological features at SRP and survival after SRP. Preoperative SII could help identify patients who might benefit from novel imaging modalities, multimodal therapy or a closer posttreatment surveillance.
Keywords: Leukocyte Count; senioři; trombocyty; proporcionální rizikové modely; Proportional Hazards Models; Preoperative Period; Inflammation; prostatektomie; počet lymfocytů; počet trombocytů; Retrospective Studies; Lymphocytes; Prognosis; zánět; Middle Aged; mužské pohlaví; nádory prostaty; Lymph Nodes; lymfocyty; Neoplasm Recurrence, Local; míra přežití; Neutrophils; Salvage Therapy; lokální recidiva nádoru; multivariační analýza; Platelet Count; Radiotherapy, Intensity-Modulated; Lymphocyte Count; brachyterapie; Multivariate Analysis; Neoplasm Staging; předoperační období; prognóza; Prostatic Neoplasms; retrospektivní studie; Humans; záchranná terapie; Prostatectomy; radioterapie s modulovanou intenzitou; Survival Rate; neutrofily; Brachytherapy; lidé středního věku; lymfatické uzliny; počet leukocytů; staging nádorů; Blood Platelets; Aged; lidé; Male